Chemical exposure and flammability risks of upholstered furniture. (28th September 2020) - Harris, Debra; Davis, Aika; Ryan, Peter Barry; Cohen, Jordan; Gandhi, Pravinray; Dubiel, David; Black, Marilyn
SUMMARY: Upholstered furniture remains a consumer fire hazard. Flame retardant technologies are necessary but may present a health risk from chemical exposure. This study developed methodologies for measuring exposure to flame retardants and flammability performance, comparing the effectiveness of differing flammability reduction strategies on upholstered chairs with and without added flame retardants and the use of a barrier material. The chemical analysis focused on volatile organic compounds (VOCs) and flame retardants. Open flame tests were conducted on chair assemblies, and smolder resistance tests were conducted on chair materials. Results showed that VOC inhalation exposure during consumer use was low for all chair types. However, VOCs were significantly elevated during the chair burns. The organophosphorus flame retardant used in this study was found in air, settled dust and dermal transfer samples. The chairs with a barrier material demonstrated significantly lower flammability hazards when compared to the other chair types. All assembled chairs did not meet the criteria for smolder testing, suggesting a lack of correlation with open‐flame performance. This study demonstrated that combined human health and flammability advantages may be achieved for upholstered chairs constructed with an effective fire barrier material without any added flame retardants.